Subfoveal choroidal thickness following pars plana vitrectomy in tractional diabetic macular edema. Issue 3 (May 2023) - Dourandeesh, Maryam; Moeini, Mahdieh; Shaye, Zahra Abbasi; Shoeibi, Nasser; Hosseini, Seyedeh Maryam; Banaee, Touka
Purpose: To evaluate changes in subfoveal choroidal thickness (SCT) in cases of tractional diabetic macular edema (DME) after pars plana vitrectomy (PPV). Methods: This prospective study included 31 eyes of 31 patients who underwent PPV for the management of tractional DME. Best-corrected visual acuity (BCVA), SCT, and central macular thickness (CMT) were measured before the operation, as well as one, three, and six months following the surgery in the operated eyes and at baseline, as well as six months in the fellow eyes. Results: The SCT decline in eyes with tractional DME was statistically significant six months postoperatively (P = 0.009). A statistically significant decline was observed in the CMT values one, three, and six months postoperatively in eyes with tractional DME (P = 0.02, P < 0.001, and P < 0.001, respectively). There was a statistically significant improvement in the visual acuity of the affected eyes three (P = 0.047) and six months (P = 0.017) postoperatively. Conclusion: After PPV for the treatment of tractional DME, a statistically significant decrease in the CMT values is detectable from the first month after surgery, followed by the improvement of BCVA from the third month. It is worth mentioning that a decrease was found in the SCT six months postoperatively.